Periodic Epileptiform Discharges Clarified for the Nonneurologist Intensivist: Clinical Implications and Current Management. (October 2015) - Lahiri, Shouri; Boro, Alexis D.; Shiloh, Ariel L.; Milstein, Mark J.; Savel, Richard H.
Periodic epileptiform discharges (PEDs) are frequently encountered during continuous electroencephalography monitoring in the intensive care unit. Their implications and management are variable and highly dependent on the clinical context. This article is intended for the nonneurologist intensivist, reviews basic terminology and clinical implications (including causes, prognosis, and association with seizures), and suggests an approach to management. Several case vignettes are included to illustrate the clinical variability associated with PEDs.